Coronary Angiography Optimized by Optical Coherence Tomography in Patients with Coronary Artery Disease - Klara Đambić; Zorin Makarović (Southeastern European Medical Journal, 2025)
The aims of the study: The aims of this study were to examine whether there is a difference in the clinical findings of the lesion obtained by coronary angiography and OCT and to examine the association of OCT findings in the decision-making on additional optimization of PCI.